Aplikasi Variasi Konsentrasi Media MS dan Thidiazuron pada Induksi Kalus Pucuk Jati (Tectona grandis) Secara In Vitro - Arsyad, Mirza Arsiaty; Immalasari, Nur Reski; Larekeng, Siti Halimah (Journal Galung Tropika, 2020)
Teak (Tectona grandis) is one of the leading tree species in Indonesia with a very high economic value. This study's objective was to determine the proper concentration of Murashige and Skoog (MS) media, and Thidiazuron (TDZ) for in vitro callus induction of T. grandis shoots. The design used was a Completely Randomized Design (CRD) factorial experiment. The first factor was the concentrations of MS media (1/2MS and MS full strength). The second one was TDZ concentrations consisted of five levels, i.e 1, 2, 3, 4, and 5 ppm. The best medium observed was M2T2 ((½ MS + 2 ppm TDZ), which successfully induced yellowish-white and whitish-green compact calli on all evaluated explants in 16,25 days with 55% of browning explants. Overall, the media being assessed can be used for callus induction on T. grandis shoots.